Naloxone dosing in the era of ultra-potent opioid overdoses: a systematic review. Issue 2 (March 2020) - Moe, Jessica; Godwin, Jesse; Purssell, Roy; O'Sullivan, Fiona; Hau, Jeffrey P.; Purssell, Elizabeth; Curran, Jason; Doyle-Waters, Mary M.; Brasher, Penelope M.A.; Buxton, Jane A.; Hohl, Corinne M.
ABSTRACT: Objectives: Evaluate the relationship between naloxone dose (initial and cumulative) and opioid toxicity reversal and adverse events in undifferentiated and presumed fentanyl/ultra-potent opioid overdoses. Methods: We searched Embase, MEDLINE, Cochrane Central Register of Controlled Trials, DARE, CINAHL, Science Citation Index, reference lists, toxicology websites, and conference proceedings (1972 to 2018). We included interventional, observational, and case studies/series reporting on naloxone dose and opioid toxicity reversal or adverse events in people >12 years old. Results: A total of 174 studies (110 case reports/series, 57 observational, 7 interventional) with 26, 660 subjects (median age 35 years; 74% male). Heterogeneity precluded meta-analysis. Where reported, we abstracted naloxone dose and proportion of patients with toxicity reversal. Among patients with presumed exposure to fentanyl/ultra-potent opioids, 56.9% (617/1, 085) responded to an initial naloxone dose ≤0.4 mg compared with 80.2% (170/212) of heroin users, and 30.4% (7/23) responded to an initial naloxone dose >0.4 mg compared with 59.1% (1, 434/2, 428) of heroin users. Among patients who responded, median cumulative naloxone doses were higher for presumed fentanyl/ultra-potent opioids than heroin overdoses in North America, both before 2015 (fentanyl/ultra-potent opioids: 1.8 mg [interquartile interval IQI, 1.0, 4.0]; heroin: 0.8 mg [IQI, 0.4, 0.8]) and after 2015 (fentanyl/ultra-potent opioids: 3.4 mg [IQI, 3.0, 4.1]); heroin: 2 mg [IQI, 1.4, 2.0]). Where adverse events were reported, 11% (490/4, 414) of subjects experienced withdrawal. Variable reporting, heterogeneity and poor-quality studies limit conclusions. Conclusions: Practitioners have used higher initial doses, and in some cases higher cumulative naloxone doses to reverse toxicity due to presumed fentanyl/ultra-potent opioid exposure compared with other opioids. High-quality comparative naloxone dosing studies assessing effectiveness and safety are needed.